Brand Preference of Smartphone - Sanju Kumar Singh; Jitendra Prasad Upadhyay (Universitas Prasetiya Mulya, 2023)
The research aims at finding out the factors that majorly influence the buying decision of a customer when choosing a Smartphone. This research used quantitative method. In this study populations for this people residing inside Kathmandu valley who were using mobile phones. The sample size of 270 respondents who were job holders and using mobile phones were surveyed based on one of the non-probability sampling techniques, the convenience sampling method. This research used independent variables, advertisement, brand image, brand loyalties, price satisfaction and attributes. In addition, variables Price has positive and significant effect on brand preferences but remaining variables, advertisement, brand image, brand loyalties positive but not significant effect. Finally, Prices Factors one of dominant variables that makes people thinks to choose the smartphones in Kathmandu City.